1999
DOI: 10.1080/10903129908958967
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of spinal immobillzatlon

Abstract: This study confirmed the previously reported respiratory restriction caused by spinal immobilization. Vacuum mattresses are more comfortable than wooden backboards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 11 publications
0
56
1
2
Order By: Relevance
“…Pain is almost universal with the use of a backboard. 22−25 There are other potential problems, such as mild respiratory compromise 26 , increased intracranial pressure, 27,28 or the rare cases of distracting an unstable fracture. 29,30 A recent pediatric study demonstrated that immobilized children with a similar level of trauma had higher rates of pain and were more likely to undergo radiographic evaluation and admission to the hospital.…”
mentioning
confidence: 99%
“…Pain is almost universal with the use of a backboard. 22−25 There are other potential problems, such as mild respiratory compromise 26 , increased intracranial pressure, 27,28 or the rare cases of distracting an unstable fracture. 29,30 A recent pediatric study demonstrated that immobilized children with a similar level of trauma had higher rates of pain and were more likely to undergo radiographic evaluation and admission to the hospital.…”
mentioning
confidence: 99%
“…There have been several studies on the effects of spinal immobilization on pulmonary function, and these studies have shown that forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity (FVC) levels significantly decreased at the 5 th and 30 th minutes (18)(19)(20). In our study, secondary indicators of pulmonary function, breath rate, and oxygen saturation were also assessed, and it was shown that they were not affected by spinal immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…[13] An experimental study on healthy subjects supine on the spinal board with standard torso straps demonstrated a significant reduction in FVC and FEV1. [14] In a study of Totten, [15] whole body immobilization either with a backboard or vacuum mattress and collar significantly restricted ventilation when compared with no immobilization. The effects were similar under the two immobilization conditions, although the FEV1 was lower on the vacuum mattress.…”
Section: Discussionmentioning
confidence: 99%